Perceptions towards the Quality of Public Services in Romania. Poor Outcomes of Public Administration Reforms? - Petrescu, Claudia; Mihalache, Flavius (Calitatea Vieții, 2020)
Public services represent an important dimension of quality of society, as they create the contextual conditions for people to further their quality of life. Romanian public administration reform has brought about a constant institutional transformation, which has influenced both the specific features and the quality of the services. This article aims to analyse trends regarding the perceived quality of public services in Romania, in European comparative perspective, using the data of the European Quality of Life Survey (2003–2016). The article aims to understand the low satisfaction with public services in Romania against the background of the public service reform measures taken by government in this period. The article describes the context of Romanian public administration and public service reform, the most important public policy measures adopted and the most important challenges. The lack of vision in the public service reform, the partial introduction of reform elements, the permanent and, sometimes, conflicting changes are issues that may have influenced the way in which the population perceives the quality of public services. The decentralisation process of public services and the insufficient allocation of public funds for delivering such services at local level might have an impact on their quality and quantity perceived by the population.